Yazd Medical Interns\' Knowledge on Legal Rules and Religious Orders in Medicine - Ehsan Fotuhi Ardekani; Mohammad Salehi; Nasrollah Bashardoost; Shiva Yasini; Hamidreza Soltani (مجله ایرانی آموزش در علوم پزشکی, 2010)
Introduction: In addition to precise physical examination and objective observations, it is necessary for students and interns to be knowledgeable about the rules and religious orders in medicine. This study was performed to investigate Yazd interns' knowledge on religious orders and legal rules in medicine. Methods: In this descriptive study performed in educational health centers of Yazd, 120 interns selected through census sampling were asked about religious orders and legal rules in medicine using a researcher made questionnaire. Data was analyzed by SPSS software using descriptive statistics and chi² test. Results: Fourteen point three percent of interns had knowledge about religious orders and legal rules Among which, 11.8% had knowledge about legal rules and 14.6 about religious orders. Seventy two percent had faced with cases about which did not know the related rules. Eighty three point two percent believed that academic courses of medical education did not provide enough information to resolve many problems. Level of their knowledge showed no significant relationship with demographic features. Conclusion: Interns' knowledge about religious orders and legal rules was in an average level. It is recommended to increase the content of medical curriculum regarding medical ethics and related issues.